2022
DOI: 10.3389/ftox.2022.881235
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Risk Assessment of the Anti-Androgen Flutamide Including the Contribution of Its Active Metabolite Hydroxyflutamide

Abstract: In next generation risk assessment (NGRA), non-animal approaches are used to quantify the chemical concentrations required to trigger bioactivity responses, in order to assure safe levels of human exposure. A limitation of many in vitro bioactivity assays, which are used in an NGRA context as new approach methodologies (NAMs), is that toxicokinetics, including biotransformation, are not adequately captured. The present study aimed to include, as a proof of principle, the bioactivity of the metabolite hydroxyfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The present study focusing on estrogenicity and a previous study focusing on anti-androgenicity (van Tongeren et al 2022 ) showed that the DCR approach can offer a relatively quick analysis on the safety of a defined exposure scenario regarding biological endpoints of which corresponding in vitro bioactivity assays are available. In NGRA, a tiered workflow could be followed when an exposure to a (novel) compound is to be evaluated.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The present study focusing on estrogenicity and a previous study focusing on anti-androgenicity (van Tongeren et al 2022 ) showed that the DCR approach can offer a relatively quick analysis on the safety of a defined exposure scenario regarding biological endpoints of which corresponding in vitro bioactivity assays are available. In NGRA, a tiered workflow could be followed when an exposure to a (novel) compound is to be evaluated.…”
Section: Discussionsupporting
confidence: 53%
“…When using the three in vitro bioactivity assays in the DCR approach, this contribution to the estrogenicity may not be captured so that the observed in vitro toxicity of a parent compound may underestimate the toxicity in the human body. This issue can be overcome by using PBK models describing the kinetics of a parent compound and its respective relevant metabolites in humans enabling the prediction of the corresponding combined internal concentrations in parent compound equivalents (Mendez-Catala et al 2021 ; van Tongeren et al 2022 ; Wang et al 2020 ). Furthermore, co-incubation with liver S9 fraction in the in vitro bioactivity assays (Mollergues et al 2017 ) offers the opportunity to evaluate whether a compound will be converted to hepatic metabolites and whether they would be more potent to the corresponding biological target.…”
Section: Discussionmentioning
confidence: 99%
“…When using the three in vitro bioactivity assays in the DCR approach, this contribution to the estrogenicity may not be captured so that the observed in vitro toxicity of a parent compound may underestimate the toxicity in the human body. This issue can be overcome by using PBK models describing the kinetics of a parent compound and its respective relevant metabolites in humans enabling the prediction of the corresponding combined internal concentrations in parent compound equivalents (Mendez-Catala et al, 2021;van Tongeren et al, 2022;Q. Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Following physiologically based kinetic (PBK) modelling-based quantitative in vitro to in vivo extrapolation (QIVIVE) (Fabian et al, 2019;Louisse et al, 2017;Punt et al, 2019;Rietjens et al, 2011;Wetmore et al, 2015;Yoon et al, 2012), the in vitro concentration-responses of T and DHT in the presence of hepatic biotransformation can be transformed to the corresponding doseresponses for the androgenic effects in humans, to set the PoD. Another method to reflect hepatic biotransformation and thus the contribution of relevant metabolites to the in vivo bioactivity of the parent compound is using a toxic equivalency factor (TEF) approach in PBK modelling-based (QIVIVE) of the parent compound (van Tongeren et al, 2022). Other advantages of the two-chamber co-culture system with human liver and reporter cells is its applicability as a high-throughput screening tool of (anti)androgenic compounds, giving insight into both toxicokinetics and toxicodynamics.…”
Section: Discussionmentioning
confidence: 99%